1995
DOI: 10.1093/infdis/171.4.1042
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Chemically Synthesized Verotoxin (Shiga-like Toxin) Pk-Trisaccharide Receptors Attached to Chromosorb for Preventing Hemolytic-Uremic Syndrome

Abstract: A double-blind, placebo-controlled study was conducted to document possible side effects associated with oral consumption of synthetic verotoxin (VT, shiga-like toxin) Pk-trisaccharide receptor sequences attached to Chromosorb (Synsorb-Pk) by healthy adult volunteers. Synsorb-Pk reclaimed from volunteer stool samples was also analyzed to determine if its VT-binding activity was affected by exposure to the pH extremes and digestive processes of the human gastrointestinal tract. No participant reported any Synso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 10 publications
0
72
0
Order By: Relevance
“…Theoretically, our findings would support the recently proposed antiadhesive therapies aimed at blocking the binding of Stx to its glycosphingolipid receptor. 62,63 BLOOD, 15 MAY 2001 ⅐ VOLUME 97, NUMBER 10 For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, our findings would support the recently proposed antiadhesive therapies aimed at blocking the binding of Stx to its glycosphingolipid receptor. 62,63 BLOOD, 15 MAY 2001 ⅐ VOLUME 97, NUMBER 10 For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…MCO moiety is similar in length to a ceramide of Gb3. A recently completed double-blind, placebo-controlled phase I study in healthy adult volunteers has revealed the safety and stability of Synsorb Pk in the human gut (2).Further, a phase II study has been completed, and a phase III study is now ongoing (3). Information of the clinical trials prompted us to evaluate the potential of Synsorb Pk for use in patients with STEC infections in Japan.…”
mentioning
confidence: 99%
“…In the course of this meeting, the clinical, epidemiological and biological features of shigellosis and STEC infections will be thoroughly reviewed, highlighting the prospects for developing new control measures. With respect to the Shiga toxins there are already clinical trials underway to fully examine the potential of adsorption of toxin in the intestinal lumen using a nonabsorbable receptor analogue (Synsorb-pk) (62). This strategy aims at blocking toxin uptake to the systemic circulation by irreversibly binding toxin to a silica particle that will be excreted in the stool, however the toxin pool present in the bowel lumen may be of limited importance in pathogenesis, as the small amount of toxin needed for systemic manifestations may be absorbed directly at the site of the intimate attachment of the organisms to the mucosa.…”
Section: Introductionmentioning
confidence: 99%